2014
DOI: 10.1021/nn500155e
|View full text |Cite
|
Sign up to set email alerts
|

Devitrite-Based Optical Diffusers

Abstract: Devitrite is a novel material produced by heat treatment of commercial soda-lime-silica glass. It consists of fans of needle-like crystals which can extend up to several millimeters and have interspacings of up to a few hundred nanometers. To date, only the material properties of devitrite have been reported, and there has been a distinct lack of research on using it for optical applications. In this study, we demonstrate that randomly oriented fans of devitrite crystals can act as highly efficient diffusers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 13 publications
2
42
0
Order By: Relevance
“…Fig. 29 Compared to common spherical particles, the core-shell structure can achieve a better light-diffusing effect due to multiscattering. 2(c).…”
Section: Morphology and Diffusing Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 29 Compared to common spherical particles, the core-shell structure can achieve a better light-diffusing effect due to multiscattering. 2(c).…”
Section: Morphology and Diffusing Mechanismmentioning
confidence: 99%
“…Haider Butt et al 29 reported a devitritebased optical diffuser with good diffusing effect. Current research on optical diffusers mainly focuses on exploring and studying anisotropic materials.…”
Section: Introductionmentioning
confidence: 99%
“…4,8 Most diffusers consist of surfacerelief structures including microlenses, pyramids, and textured surfaces due to the simplicity and time required for their fabrication. [9][10][11][12][13] Optical diffusers have been fabricated employing a range of coating processes. 5,14 However, nanosecond pulsed laser patterning of optical diffusers have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, the crystalline counterparts have also found quite a number of applications in Materials science. Na 2 CaSiO 4 or Na 2 Ca 2 Si 3 O 9 (combeite), for example, have been reported as major phases in bioactive glass ceramics or as host materials for inorganic phosphors, whereas overlapping fans of needles of Na 2 Ca 3 Si 6 O 16 (devitrite) crystals have been successfully developed for manufacturing of low-cost optical diffusers (Kaygili 2014;Fujikura et al 2012;Liu et al 2014;Butt et al 2014). The corresponding potassium system, on the other hand, has seen a revival of interest only recently.…”
Section: Introductionmentioning
confidence: 99%